Política nacional de enfrentamento às drogas no Brasil: novas estratégias a partir da análise dos pontos de desarticulaçāo do programa Crack, é possível vencer - Worm, Naíma (Universidade Presbiteriana Mackenzie, 2017)
This research is about the study of coping with public policies on drugs adopted in Brazil, aiming to present the legal strategies that support the political entities to create confronting programs to crack. In the survey the normative base that supports the drug policy was used, especially the federal government Crack program, it's possible to win, of national extensive and adopted in all the capitals of the states and cities with a population over 200,000 inhabitants. In chapter one the models to confronting drugs were presented - prohibitionist, abolitionist and harm reduction models - in order to support the study of the Crack program, it is possible to win and present strategies to be used in any confrontation program to crack. The protection of social rights under the Federal Constitution of 1988 was analyzedas well as the specific protection to health and social care. The second chapter investigated the legal theory about public policies and the conceptual foundations of public drug policies as well as the controversy over the non-voluntary hospitalization and the first user profile mapping and crack addicts in the country conducted by the Oswaldo Cruz Foundation. Chapter three described the structural axes of the Crack program, it's possible to win, analyzing the dismantling of parts of the program that compromise its full realization, as it is the main topic of the thesis. Finally, in chapter four, proposals for re-articulation of the program were built, in order to contribute to further studies and subsidize possible interventions in public policy drug running. The methodology used in the research is deductive, with the application of documentary research techniques and theoretical framework, investigating the theory that supports the construction of public policies and normative basis and document the Crack program, it's possible to win. The conclusions drawn from the proposed issue presented as dislocation point of the program: the need for prior diagnosis for identifying the public to be served and size of the actions; expansion of the program in order to include cities with less than 200,000 inhabitants; need for civil society participation in planning and program implementation; lack of interest of municipal managers in joining the program; difficulty understanding among the three structural axes of the program: care, authority and prevention; precarious UHS networks - Unified Health System and USSA - Unique System of Social Assistance; need for expansion of the sectors that make up the program; monitoring and evaluating the program and insufficient financial investment for their implementation.